2016
DOI: 10.1007/s12639-016-0764-7
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomalaria in a domestic pigeon: a case report

Abstract: Microscopic examination of thin blood smear of a domestic pigeon brought to Teaching Veterinary Clinical Complex, Junagadh, Gujarat revealed mature and immature halter shaped gametocytes of Haemoproteus columbae encircling the nucleated erythrocytes. The disease was diagnosed as acute infection of pigeon malaria more notably known as pseudomalaria. The parasitic infection was further confirmed by polymerase chain reaction assay targeting the Cytochrome b (cyt b) gene fragment amplifying 207 base pair (bp) frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The regional variation in H. columbae prevalence in pigeons is primarily influenced by vector abundance, in which our study confirms the presence of Pseudolynchia canarenisis. Clinical symptoms of H. columbae infection include anorexia, lethargy, depression, dyspnea, circling movement, and diarrhoea (Maharana and Kumar, 2016) which is in agreement with our study. Chloroquine, an antimalarial drug, is utilised to treat Haemoproteus sp.…”
Section: Treatment and Discussionsupporting
confidence: 93%
“…The regional variation in H. columbae prevalence in pigeons is primarily influenced by vector abundance, in which our study confirms the presence of Pseudolynchia canarenisis. Clinical symptoms of H. columbae infection include anorexia, lethargy, depression, dyspnea, circling movement, and diarrhoea (Maharana and Kumar, 2016) which is in agreement with our study. Chloroquine, an antimalarial drug, is utilised to treat Haemoproteus sp.…”
Section: Treatment and Discussionsupporting
confidence: 93%
“…Multivitamin liquid (Vimeral, Virbac Animal Health India Pvt. Ltd., Mumbai) at the rate of 0.2 ml per os, twice daily for 2 weeks, in drinking water, was supplemented as it removes stress and enhances immunity (Maharana and Kumar 2016). The vectors for H. columbae were controlled by changing the litter regularly, and treating the pigeon shelter with Deltamethrin (Butox, MSD Animal Health, Pune) spray at a dilution rate of 2 ml/l of water (Varshney et al 2014;Raval et al 2016).…”
Section: Treatmentmentioning
confidence: 99%
“…It is a fatal infection of young and stressed pigeons, however, in adult birds, it is non-pathogenic. The clinical signs of H. columbae infection include anorexia, lethargy, depression, dyspnea, circling movement and diarrhea (Zinkl 1986;Varshney et al 2014;Maharana and Kumar 2016). The prevalence rate of H. columbae infection in pigeons is higher in Indian states, namely Kerala and Gujarat (Ravindran et al 1999;Raval et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Haemoproteus columbae, transmitted by hippoboscid 'louse' ies, which causes "pseudo malaria" is the most common hemoparasite isolated from pigeons [5,6]. Prevalence of pseudo malaria in pigeon populations is variable from 27.6% to 100% and may be lethal to young pigeons [7][8][9]. Leucocytozoonosis is understudied and seems to have a low prevalence in pigeons as well, according to a study from Italy which reported a prevalence of only 15.7% [10].…”
Section: Introductionmentioning
confidence: 99%